NEUROMODULATION AND THE ORCHESTRATION OF THE RESPIRATORY RHYTHM - Doi, Atsushi (2008)
The respiratory system is continuously modulated by numerous aminergic and peptidergic substances that act at all levels of integration: from the sensory level to the level of central networks and motor nuclei. The same neuronal networks receive inputs from multiple modulators released locally as well as from distal nuclei. All parameters of respiratory control are controlled by multiple neuromodulators. By partly converging onto similar G-proteins and second messenger systems, acetylcholine, norepinephrine, histamine, serotonin (5-HT), dopamine, ATP, substance P, cholecystokinin (CCK) can increase frequency, regularity and amplitude of respiratory activity. Yet, the same modulator can also exert differential effects on respiratory activity by acting on different receptors partly in the same neurons. In the pre-Bötzinger complex (pre-BötC) modulators can differentially modulate frequency and amplitude in different types of pacemaker neurons. Similarly motoneurons located in different motor nuclei receive differential amplitude modulation from different modulators. Thus, modulators are capable of orchestrating and modulating different parameters of respiratory activity by differentially targeting different cellular targets. A disturbance in modulatory control may lead to Sudden Infant Death Syndrome (SIDS) and erratic breathing.